2017
DOI: 10.4314/sajas.v47i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of various feeding programmes on growth performance, carcass and meat qualities of Thai indigenous crossbred chickens

Abstract: This study was conducted to evaluate the effects of various feeding programmes on growth performance, carcass characteristics, and the meat qualities of Thai indigenous crossbred (50%) Korat chickens to obtain suitable feeding programmes. A total of 480 one-day-old mixed-sex Korat chickens were randomly allotted to four treatments, namely FP1, FP2, FP3 and FP4, with four replicates for each treatment (30 birds per replicate) in a completely randomized design. Chickens in FP1 were fed diets with 21, 19, 17 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 20 publications
(23 reference statements)
2
13
0
Order By: Relevance
“…The cholesterol content of Sensi-1 Agrinak chicken meat was not affected by dietary CP and ME levels. The current study was in tune with the result of study which shown by Maliwan et al (2017) in Thai indigenous crossbred chicken (Korat chicken) which reported that the feeding program was given different dietary CP levels (15,17,19,21% CP) during the growth period (0-10 weeks), affected no different meat chemical composition (moisture, protein, and cholesterol). Brewer et al (2012) reported that studies which had been done to attempt with several feeding programmes using many dietary CP levels, showed that all the programs did not affect meat quality.…”
Section: Resultssupporting
confidence: 73%
“…The cholesterol content of Sensi-1 Agrinak chicken meat was not affected by dietary CP and ME levels. The current study was in tune with the result of study which shown by Maliwan et al (2017) in Thai indigenous crossbred chicken (Korat chicken) which reported that the feeding program was given different dietary CP levels (15,17,19,21% CP) during the growth period (0-10 weeks), affected no different meat chemical composition (moisture, protein, and cholesterol). Brewer et al (2012) reported that studies which had been done to attempt with several feeding programmes using many dietary CP levels, showed that all the programs did not affect meat quality.…”
Section: Resultssupporting
confidence: 73%
“…Both parameters are involved in protein metabolism, and a lower concentration mainly in restricted females might be affected by a lower liver protein synthesis, which decreases plasma protein concentration (Rajman et al, 2006). Maliwan et al (2017) suggested that urea concentration corresponds with growth performance, and in the present study, DWG was higher in the ADL groups. A short feed restriction period has a minor effect on the blood picture, with only the LY number being higher in the restricted cockerels, which agrees with the authors' results with rabbits (Tůmová et al, 2007;Chodová et al, 2017).…”
Section: Discussionsupporting
confidence: 53%
“…A KKU 1 chicken is an indigenous hybrid chicken breed, developed by the Network Center for Animal Breeding and Omics Research. Thai broiler chickens have a terminal hybrid of 75% commercial broiler breed and 25% of Thai native chicken breed [14].…”
Section: Animals and Experimental Designmentioning
confidence: 99%